Martyrdom and sacrifice in Islam theological, political and social contexts - Hatina, Meir; Litvak, Meir (Library of modern religion, 2017)
Martyrdom in the Muslim world is increasingly integral to conversations about international security. Over the years, the belief system around self sacrifice has become key to understanding the Middle East and its political relationships with the West, although much of the literature and conversation has been restricted to modern concepts of jihadism. The recent spate of scholarship relating to suicide bombers and jihadists studies these concepts without a broader understanding of the principle of martyrdom. This work expands on the chronology of self-sacrifice within Islam and contextualises the use of suicide bombings using details of the rise of martyrdom in places such as Iraq, Lebanon, Chechnya and Pakistan. It historicises the background in which 'jihad' has been glorified while also exploring contemporary methods of recruitment, like the use of the Internet.